The distribution of particle size and composition of manganese nodule comminuted during lifting - Yoon, C.; Kim, J.; Park, H.; Yoo, Kyoungkeun (Taylor & Francis, 2015)
The effect of grinding time on the particle size distribution and chemical composition of manganese nodule was investigated to provide information such as the density and the metal contents of Mn, Fe, Ni, and Co for efficient design of separation process on ship. Therefore, the manganese nodules obtained from Pacific Ocean were ground with the mortar and ball mill, and then the density and the contents of metals were measured with particle size. In the mortar grinding test, the density and Mn contents of the ground product increased as the particle size increased indicating that the smaller particle contains less metallic components. In the ball milling test, the weight distribution of particle with less than 150 µm increased from 2.6 to 18.8% with the grinding time from 20 to 180 min, respectively. In the particle range with – 150 µm, the contents of Mn and Ni increased with increasing grinding time, whereas there is a little difference in the Fe and Co contents with the grinding time. The increase in density with grinding time resulted from the increase in the contents of Mn. These kinds of information are useful to design the efficient separation process on ships.